Influence of Chip Formation Characteristics on Flank Contact Load Distribution in Titanium Alloy Cutting; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Kozlov V. N. Victor Nikolayevich (Mechanical Engineering, Processing and Surface Engineereng, Metals Treatment, Equipment and Tools, 2015)
Title screen